Um estudo de caso da escolarização de textos lidos e produzidos em contexto acadêmico - Elizabeth Maria da Silva (2017)
Situated in the scope of studies on academic literacy, this thesis arises from the desire to examine contexts of production and circulation of texts read and produced in the academic field, considering the literacy practices to which they are related. For this, I developed an investigation with the aim of exploring the meanings of academic literacy in two specific contexts: Pedagogy and Psychology courses at the Federal University of Minas Gerais (UFMG). I focused particularly on how professors and students in these courses characterized theliterate actions (CASTANHEIRA; GREEN; DIXON, 2007) developed in theclassroom: reading, requesting, producing and evaluating written texts. For this, I considered the assumptions of the New Literacy Studies (NLS) group (GEE, 1996 [1990]; STREET, 1984, 1993) and the Academic Literacies (LEA; STREET, 1998). Based on the vision of reading and writing as social practices. Adopting principles of the qualitative approach (BOGDAN; BIKLEN, 1994) and exploring elements of an ethnographic perspective (GREEN, BLOOME, 1995), I developed semi-structured interviews (SPRADLEY, 1979; PATAI, 1988) with professors and students, and examined texts written by students. By exploring such data sources, based on discursive choices (IVANIC, 1994) and on contextualizationcues (GUMPERZ, 2002 [1982]), I showed that the literate actions(CASTANHEIRA; GREEN; DIXON, 2007) characterized by the participants are aligned, with different nuances, to a schooling literacy practice. Data analysis showed that, althought participants referred to different genres of discourse, when texts were introduced in class, they were transformed into objects of teaching: the students read or write to achieve, in general, certain pedagogical objectives, defined by the professor, privileged reader of the texts, who read them, in most cases, to evaluate the students' learning. I reflected that schooling of texts, while unavoidable, is not in itself a negative thing, but it is how it happens that can be productive or not. Finally, I pointed out the "teaching critical genre awareness" pedagogy (DEVITT, 2009), as well as the establishment ofinterdisciplinary dialogue as viable alternatives to explore reading and writing as social practices, contributing to the expansion of students and professors academic literacies.